2012
DOI: 10.1111/j.2042-3306.2011.00509.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of admission L‐lactate concentration in hospitalised equine neonates with presenting complaint, periparturient events, clinical diagnosis and outcome: A prospective multicentre study

Abstract: SummaryReasons for performing the study: Admission L-lactate concentration is a useful and commonly measured biomarker not previously prospectively evaluated in a large multicentre study of critically ill neonatal foals. Objectives: To evaluate overall outcome and the association of survival and L-lactate concentration at admission ([LAC]ADMIT) by periparturient history, presenting complaint and clinicians' major diagnosis for ill neonatal foals. Methods: Thirteen university and private equine referral hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
58
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(68 citation statements)
references
References 36 publications
8
58
1
1
Order By: Relevance
“…In our study, slight changes to the current modified sepsis score of some variables (eg, blood glucose concentration) as well as the addition of new variables (eg, blood l ‐lactate concentration, serum creatinine concentration, lymphocyte count, SIRS) did not improve sensitivity or specificity when compared with the modified sepsis score . Although these additional variables have been significantly associated with sepsis, their addition to the sepsis score failed to improve the diagnostic quality of the scoring system . The sensitivity and specificity of the modified sepsis score in this foal population (62% and 64%, respectively) were similar to what was found in previous studies that evaluated the modified sepsis score in 2015 (56.4% and 73.4%, respectively) and 2003 (67% and 76%, respectively), but were lower than results of a 1984 report (92.8% and 87.5%, respectively) .…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…In our study, slight changes to the current modified sepsis score of some variables (eg, blood glucose concentration) as well as the addition of new variables (eg, blood l ‐lactate concentration, serum creatinine concentration, lymphocyte count, SIRS) did not improve sensitivity or specificity when compared with the modified sepsis score . Although these additional variables have been significantly associated with sepsis, their addition to the sepsis score failed to improve the diagnostic quality of the scoring system . The sensitivity and specificity of the modified sepsis score in this foal population (62% and 64%, respectively) were similar to what was found in previous studies that evaluated the modified sepsis score in 2015 (56.4% and 73.4%, respectively) and 2003 (67% and 76%, respectively), but were lower than results of a 1984 report (92.8% and 87.5%, respectively) .…”
Section: Discussionsupporting
confidence: 63%
“…Since the introduction of the modified equine sepsis score, more recent studies have identified updated or additional variables that have potential association with neonatal sepsis . For example, the median l ‐lactate concentration in septic foals (4.8 mmol/L) was significantly higher than that of nonseptic foals (3.3 mmol/L) in a large prospective study .…”
Section: Introductionmentioning
confidence: 99%
“…A recent study of 643 equine neonates performed during the 2008-2009 foaling season at 13 university or private referral hospitals revealed an overall survival of 79% [5]. This proportion of survivors is considerably higher than those reported in other intensive care units in the 1980s (59%) or 1990s (68%) [3,4].…”
Section: Discussionmentioning
confidence: 88%
“…38 Critically ill foals likely have both type A and type B hyperlactatemia. 37,38 In the study reported here, the mean blood lactate concentration was significantly lower at 4 and 5 hours in the polymyxin B group, compared with the control group. Although the exact metabolic alterations causing hyperlactatemia were not examined in this study, this information suggested that treatment of neonatal endotoxemia with polymyxin B potentially improves systemic oxygenation or abates factors associated with the development of hyperlactatemia.…”
Section: 33mentioning
confidence: 82%
“…[34][35][36] Hyperlactatemia can occur via a multitude of pathophysiologic mechanisms, with the most common mechanism arising from anaerobic tissue metabolism, which occurs with an imbalance between oxygen delivery and tissue demand (type A hyperlactatemia). 37 Hyperlactatemia may also occur under conditions of adequate oxygen delivery (type B hyperlactatemia) in the face of increased or impaired oxygen utilization secondary to the systemic inflammatory response syndrome, sepsis, neoplasia, or mitochondrial dysfunction. 38 Type B hyperlactatemia can also occur from reduced lactate clearance in conditions such as liver or renal failure.…”
Section: 33mentioning
confidence: 99%